X-Wörter im Deutschen: ein Wortbildungsmuster zur diskursiven Vermeidung von Begriffen - Leonhard, Jens; Röhrs, Falko (Zeitschrift für Sprachwissenschaft, 2023)
In this paper, we investigate the German word formation pattern X-Wort within the theoretical framework of discourse morphology. For this purpose, morphological, semantic, and pragmatic analyses are combined on the basis of the German reference corpus. It is shown that the word formation pattern is productive and extremely frequent. However, the meaning of the word formation product is not always clear, since only two X-Wörter ( N-Wort and F-Wort ) can be considered lexicalized. Instead of word meanings acquired through the formation, a common function of the X-Wörter can be identified: they are used in metalinguistic discourses to avoid and mask certain terms. In this context, X-Wörter differ with respect to the motivation of avoidance: (i) racist terms, (ii) vulgar terms, and (iii) politically and superstitiously explosive words are avoided and masked. Thus, X-Wörter are part of euphemistic language. As such, their use can also be enregistered, and acquire a social-symbolic function, which indicates moral-ethical ideas of the speaker or writer. Consequently, we describe the word formation pattern as a form-meaning/function-pair whose morphological structure perfectly fits its communicative needs to avoid and mask specific words in discourses.